2019
DOI: 10.1002/jmv.25489
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of respiratory syncytial virus in western India with special reference to appropriate age for infant vaccination

Abstract: Respiratory syncytial virus (RSV) causes significant infant mortality worldwide and a vaccine may be available soon. This study determined age-stratified anti-RSV antibody positivity (enzyme-linked immunosorbent assay [ELISA]) at Pune, India (cord blood-85 years). Antibody positivity declined from 100% at birth to 71.3%(3 months), and 0.7% (6 months). A significant rise was noted at 15 months (16%), 16to 24 months (64.5%) and 4 years (95.2%) with concomitant IgM-anti-RSV positivity indicative of recent infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Anti-RSV antibodies were more in adult population because of prior exposure to RSV. 45 , 46 Percentage of population reported positive for anti-RSV antibodies is presented in Table 6 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Anti-RSV antibodies were more in adult population because of prior exposure to RSV. 45 , 46 Percentage of population reported positive for anti-RSV antibodies is presented in Table 6 .…”
Section: Resultsmentioning
confidence: 99%
“… 49 Considering significant prevalence of RSV in Indian children there is a need to provide effective interventions for the prevention of RSV which require understanding of current dynamics of maternal anti-RSV antibodies, so that necessary preventive measures can be planned and executed. Serological data in the study conducted by Arankalle et al 46 revealed that, approximately 30% of infants by the age of 3 months and almost the entire infant population by the age of 6 months is devoid of anti-RSV antibodies which indicates that children (0-6 months) need early protection with the vaccine-induced immune response. Furthermore, it is suggested that below mentioned 3 target populations would be the appropriate age groups for vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All blood samples we collected at sixth month had negative anti-RSV Ig G antibody levels. Arankalle et al [19] found that only 0.7% of babies who were all positive for RSV antibodies at birth were positive for anti-RSV antibodies at the sixth month. In another study, the infants' anti-RSV IgG antibody positivity rate at sixth month was reported as 16% [20].…”
Section: Discussionmentioning
confidence: 99%